Exploring how Parents can Promote Gender Diversity in South African High Schools - John , Chaka; Henry , Nichols (Journal of Ecohumanism, 2024)
By examining the voices of parents regarding the extent to which South African high schools maintain a cisnormative culture, this paper aims to explore how parents' understanding of gender can play a role in promoting gender diversity. Drawing on a qualitative study conducted in the Free State Province of South Africa and framed by both Queer Theory and the African philosophy of Ubuntu. A focus group interview was employed to interview nine parents. Consistent with many international studies on the experiences of parents regarding gender diversity in high schools, this paper found that most of the parents’ views were influenced by cultural and religious backgrounds. The results reveal that parents' understanding of gender can play a role in promoting gender diversity in South African high schools. Results further reveal an emerging understanding that gender diversity is real, not mythical. This paper calls for more research to examine how parents can help others to embrace gender diversity through various school platforms to accelerate parental support of trans learners. Lastly, the Department of Basic Education can formulate a policy that will assist schools in engaging parents to support schools in promoting gender diversity.